Profitability Ratio, CSR, and ESG Disclosure on The Stock Performance Of Financial Companies - Aisyah, Siti Nur; Yunia, Risa (Universitas Islam Kadiri, 2025)
Sustainability has become a key strategy in the global business world to build stakeholder trust and maintain competitiveness in an increasingly competitive market. This study aims to analyze the impact of the disclosure of profitability ratios (ROA, NPM, and EBIT), Corporate Social Responsibility (CSR), and Environmental, Social, and Governance (ESG) on stock performance in the financial sector. The research employed a purposive sampling technique and was analyzed using panel data regression with STATA version 17. The best model was selected using the Chow test and Hausman test. This study is based on Stakeholder Theory, which emphasizes the importance of corporate responsibility toward stakeholders, as well as Signaling Theory, which suggests that financial and sustainability information serves as a signal to investors. The results show that ROA, NPM, and ESG have a positive impact on stock performance, while EBIT and CSR do not show a positive effect. These findings indicate that strategies to improve stock performance in the financial sector should focus on efficient asset management and consistent and genuine implementation of ESG principles.